Groups Characterization for the development of a simulation technology tool, which strengthens the training process in administrative and document management programs CEGAFE - Rodríguez Parra, Rocío Del Mar
The following article presents the phase 1 results of the project “Development of a simulation technology tool in administrative procedures, which strengthens the teaching-learning processes of the Administrative and Document Management area of the SENA-CEGAFE”, which allows the characterization of a specific group. Statistical information was collected from 40 graduates, 310 apprentices and 19 instructors from the courses Technologist in Administrative Management and Technologist in Documentary Management. The information obtained provides bases to continue with the project development, whose search will allow the apprentices to strengthen their professional skills.